Primary pulmonary lymphoepithelioma-like carcinoma in non-endemic region: A case report and literature review. Issue 8 (February 2018) - Xie, Chao; Xu, Xia; Wu, Bian; Yang, Kun-Yu; Huang, Jing
Abstract: Rationale: Pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of lung squamous cell carcinoma. In situ hybridization test for Epstein–Bar virus-encoded RNA (EBER) is generally used for distinguishing it from other lung cancers. Although plasma EBV DNA quantification has been widely used as a tumor biomarker in nasopharyngeal carcinoma (NPC), only a limiting number of studies have suggested that plasma EBV DNA quantification may be used as a tumor marker in pulmonary LELC patients. Patient concerns: We report two female patients diagnosed as poorly differentiated squamous cell carcinoma, subsequently, their further histological examinations showed that tumor cells were EBER positive and plasma EBV DNA was detectable. Diagnoses: Two patients was diagnosed with advanced pulmonary LELC. Interventions: The patients were treated with chemotherapy and chemoradiotherapy respectively. Outcomes: Both patients responded well to our treatment, in accordance with their decreased EBV DNA level. Lessons: Pulmonary LELC is a rare type of lung cancer which is sensitive to chemoradiotherapy, especially in late staged patients.